(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article analyzes the conceptual and methodological foundations of modernizing the military education system under the conditions of 21st-century digital transformation and the VUCA and BANI world models. Moving away from traditional reproductive teaching methods, the study highlights the evolution of technologizing military education, drawing upon the theories of socio-constructivism, cognitive dissonance, and multimedia learning. The article provides a profound scientific justification for the military-practical integration of interactive, project-based (PBL), problem-based learning, digital technologies (AI, GIS, VBS simulators), and “Flipped Classroom” models through specific tactical examples (FPV drone attacks, hybrid threats, autonomous defense projects).